If it's not what You are looking for type in the equation solver your own equation and let us solve it.
83.2=8(m+3.3)
We move all terms to the left:
83.2-(8(m+3.3))=0
We calculate terms in parentheses: -(8(m+3.3)), so:We get rid of parentheses
8(m+3.3)
We multiply parentheses
8m+26.4
Back to the equation:
-(8m+26.4)
-8m-26.4+83.2=0
We add all the numbers together, and all the variables
-8m+56.8=0
We move all terms containing m to the left, all other terms to the right
-8m=-56.8
m=-56.8/-8
m=7+0.8/8
| 15=5/4u | | 4/7x=385 | | -25=-5/6*r | | x+2x-9+x+35+50=360 | | (X-2)(y+2)=360 | | 5(2y-5)-3(2y+3)=2(y-26) | | (Z+12)/4=(z/16) | | a/3-3/a=9a+5/27 | | -22=5v-7 | | 9v-18=-18 | | r^2+10r+21=-3 | | -(x-4)=-3x-2 | | 8(2x-4)-16=48 | | r^2=10r+21=-3 | | 2x-66=0 | | 3x^2+11=5x | | -9a=-42 | | 4(2y-3)+5(y-5)=6(y+12) | | (-11/6)+m=-(2/9) | | 10m+6=6m+8 | | 5y/12-1=8-4y/3 | | 1-x=1-4x | | 5/13=j-6/13 | | 0=-4.9t^2+150t+350 | | 12/43x=180 | | 11y/20-4=6-5y/4 | | 17v−16v=14 | | 2(2x+3)=6(x+9 | | 7(3x-5)-6(2x-4)=4x+34 | | 12/43x=189 | | 5x+4=1+2x | | 2.3y+8-3y-10=0 |